The Development of E-Book Based on Project Based Learning on the Plant Anatomy Structure Material - Desy Muwaffaqoh; Tjandra Kirana; Fida Rachmadiarti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Problem solving skills are needed by students to solve problems that arise in everyday life. Innovation in learning is needed so that students can achieve the basic competencies and apply 21st-century skills, in the form of interactive, collaborative learning models. One of the innovations is using the Project-Based Learning learning model with the E-book of plant anatomy structures. This study aims to develop an E-book of PjBL-based plant anatomy structures to practice problem-solving skills which are declared valid in terms of theoretical and empirical aspects. The theoretical aspect is viewed from the results of the validity. Empirical aspects in terms of learning outcomes, student responses, and readability. The development model used is 4D. The research was carried out at the UNESA Postgraduate Program in June-August 2020. The target of this research was an online E-book on the structure of plant anatomy based on Project Based Learning which was tested on ten students of Muhammadiyah 1 Gresik senior high school in February 2021. The instruments used were validation sheets, student response sheets, and fry chart sheets. The data were analyzed descriptively quantitatively. The results showed that the PjBL-based E-book of plant anatomical structures was theoretically feasible based on the validation results obtained an categories very valid and empirically feasible based on student learning outcomes (N-gain of moderate categories). Based on this description, a PjBL E-book of plant anatomy structures to train students' problem-solving skills is feasible theoretically and empirically.